A Survey on Factors Affecting the Development of China Logistics Industry in Shanghai - Hu, Kun (2009)
The aim of this paper is to examine factors that affect the development of China logistics industry. Chapter 1 introduces the background of China logistics industry, and the problem statements and research objectives are shown. In Chapter two, the author establishes the hypothesis as independent variables which are transportation, government regulation, warehousing and storage, IT support and infrastructure according to previous studies by researchers. Also, three measurements that are cost, productivity and expansion are given to measure the development of China logistics industry as dependent variables. Beside these, the theoretical framework shows the relationship between independent variables and dependent variables. After testing the reliability and validity of questionnaires, the researcher conducted a survey using questionnaires and interviews in Shanghai. By analyzing the received data using Spearman Test, the researcher concluded that the high transportation cost and lack of using Information Technology (IT) are two main factors that limit the development of China logistics industry. So, as recommendations, the researcher suggests using Information Technology (IT) to reduce the transportation cost in China logistics industry as a priority.